2019
DOI: 10.3390/w11040752
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Planting Density on the Growth and Yield of Sunflower under Mulched Drip Irrigation

Abstract: A field experiment was conducted to test the suitability of growing sunflower undermulched drip irrigation with saline water in the HID (Hetao Irrigation District), North China. Theexperiment included five planting densities in which the plant spacing was 30, 35, 40, 45, and 50 cmwith the same spacing (50 cm) between rows. The results indicated that mulched drip irrigationwith saline water was more water‐saving than traditional ground irrigation using fresh water, whilethe irrigation quota increased with the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 25 publications
4
7
0
1
Order By: Relevance
“…However, cultivar Hélio 251 obtained a larger leaf dry biomass at 0.45 m spacing in the micro-sprinkler and sprinkler irrigation systems, reaching 239.93 and 245.09 g, respectively. These results corroborate those described by Li et al (2019), who observed that denser spacings increased leaf biomass in sunflower plants. * Uppercase letters in the columns refer to differences between cultivars within each combination of systems and spacings; lowercase letters in the columns refer to differences between systems within each combination of cultivars and spacings; and Greek letters in the rows refer to differences between spacings within each combination of cultivars and irrigation systems, according to Tukey's test at p<0.05.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…However, cultivar Hélio 251 obtained a larger leaf dry biomass at 0.45 m spacing in the micro-sprinkler and sprinkler irrigation systems, reaching 239.93 and 245.09 g, respectively. These results corroborate those described by Li et al (2019), who observed that denser spacings increased leaf biomass in sunflower plants. * Uppercase letters in the columns refer to differences between cultivars within each combination of systems and spacings; lowercase letters in the columns refer to differences between systems within each combination of cultivars and spacings; and Greek letters in the rows refer to differences between spacings within each combination of cultivars and irrigation systems, according to Tukey's test at p<0.05.…”
Section: Resultssupporting
confidence: 92%
“…Lastly, in the sprinkler irrigation system, cultivars Hélio 251 and 360 reached the largest dry biomass of heads at 0.45 m spacing (345.62 and 290.18 g, respectively). At 0.55 m spacing, cultivar Hélio 360 obtained the largest dry biomass of heads in the sprinkler irrigation system, averaging 297.21 g. The response shown by dry biomass of heads to the spacings was similar to that observed for stem dry biomass, since smaller planting spacings in cultivars Hélio 251 and Hélio 360, under irrigation, tended to result in larger dry biomasses of heads, corroborating the findings of Li et al (2019).…”
Section: Resultssupporting
confidence: 78%
“…The height of plants with plants standing density increasing usually increases, especially with using irrigation [33]. There is also a decrease in the weight of 1000 seeds and seeds number from the anthode [34]. However, with plant density increasing, competition for light between plants increases, which leads to a decrease in vegetative and reproductive plasticity of the plant [35], while lower plant density leads to reduced light absorption by plants what leads to a reduction in yield per unit area [36] [37] [38].…”
Section: Morphological Features Of Plants Sunflower Yield Depending On Plants' Densitymentioning
confidence: 99%
“…In accordance with our results, Ibrahim (2012) declared that increasing the sunflower plant density in a range from 45,000 to 90,000 plants ha −1 resulted in significant increase in total dry matter and seed yield. In another study, Li et al (2019) after examining the inter-plants distances of 30, 35, 40, 45, and 50 cm showed that despite the reduction in seeds number per head and the 1000seed weight at high plant densities, the sunflower seed yield increased in response to increasing plant density per unit area.…”
Section: Seed Yieldmentioning
confidence: 94%